Endostatin as a biomarker of systemic sclerosis: insights from a systematic review and meta-analysis - Mangoni, Arduino A.; Zinellu, Angelo (Frontiers in Immunology, 2024)
IntroductionThe critical role played by vascular dysfunction and ineffective angiogenesis in the pathophysiology of systemic sclerosis (SSc) suggests that circulating biomarkers reflecting these alterations may be useful in the clinical evaluation of this patient group. We sought to address this issue by conducting a systematic review and meta-analysis of studies investigating a such candidate biomarker, endostatin, an endogenous glycoprotein exerting anti-angiogenic effects, in SSc patients and healthy controls.MethodsA literature search was conducted in the electronic databases Web of Science, PubMed, and Scopus from inception to 27 May 2024. Risk of bias and certainty of evidence were assessed using the JBI checklist for analytical studies and GRADE, respectively.ResultsIn 19 eligible studies, circulating endostatin concentrations were significantly higher in SSc patients than controls (standard mean difference, SMD=0.90, 95% CI 0.56 to 1.23, p<0.001; low certainty of evidence). Endostatin concentrations were also significantly higher in SSc patients with digital ulcers than those without (SMD=0.43, 95% CI 0.24 to 0.62, p<0.001; very low certainty of evidence) and in patients with pulmonary arterial hypertension than those without (SMD=1.21, 95% CI 0.67 to 1.76, p<0.001; very low certainty of evidence). By contrast, no significant differences were observed between SSc patients with limited vs. diffuse disease and those with different video capillaroscopy patterns. There was limited evidence regarding endostatin concentrations in SSc patients with interstitial lung disease, telangiectasias, and gastrointestinal manifestations. There were no significant associations in meta-regression and subgroup analysis of studies investigating endostatin in SSc patients and controls between the effect size and various patient and study characteristics.DiscussionTherefore, the results of this systematic review and meta-analysis suggest that measuring endostatin can be useful in assessing the presence of SSc and specific complications, i.e., digital ulcers and pulmonary arterial hypertension, in these patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024558174.